'Clean' hydrolase reactions using commercial washing powder. Issue 42 (2nd August 2019) - Zhang, Jie; Tonin, Fabio; Zhang, Wuyuan; Hagedoorn, Peter-Leon; Mallée, Lloyd; Hollmann, Frank
Abstract : We report the use of commercial laundry powder as a biocatalyst for a range of lipase-catalysed reactions including (trans)esterification, ester hydrolysis and chemoenzymatic epoxidation reactions. Abstract : We report the use of commercial laundry powder as a biocatalyst for a range of lipase-catalysed reactions including (trans)esterification, ester hydrolysis and chemoenzymatic epoxidation reactions. The enzymatic laundry powder exhibited excellent stability and recyclability, making it a readily available and cheap biocatalyst for chemical transformations.